2013
DOI: 10.1098/rsif.2012.0536
|View full text |Cite
|
Sign up to set email alerts
|

Applications of polymeric adjuvants in studying autoimmune responses and vaccination against infectious diseases

Abstract: Polymers as an adjuvant are capable of enhancing the vaccine potential against various infectious diseases and also are being used to study the actual autoimmune responses using self-antigen(s) without involving any major immune deviation. Several natural polysaccharides and their derivatives originating from microbes and plants have been tested for their adjuvant potential. Similarly, numerous synthetic polymers including polyelectrolytes, polyesters, polyanhydrides, non-ionic block copolymers and external st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 147 publications
(198 reference statements)
1
64
0
4
Order By: Relevance
“…Biodegradable polymers have the ability to withstand these challenges and are considered promising candidates for next generation platform vaccine development. Additionally, many polymeric vaccine adjuvants (table 2) have been found to deliver the vaccine successfully, target the immune system and effectively elicit the required immune response [43][44][45][46][47]. …”
Section: Live Attenuated Vaccinesmentioning
confidence: 99%
“…Biodegradable polymers have the ability to withstand these challenges and are considered promising candidates for next generation platform vaccine development. Additionally, many polymeric vaccine adjuvants (table 2) have been found to deliver the vaccine successfully, target the immune system and effectively elicit the required immune response [43][44][45][46][47]. …”
Section: Live Attenuated Vaccinesmentioning
confidence: 99%
“…Las NP de polianhídrido metil vinil éter comaleico (PVMA NP) utilizadas como adyuvante activan diferencialmente las DC a través de receptores TLR2 y TLR4, de manera dosis dependiente (82)(83)(84). NP basadas en quitosano prometen ser una buena opción como adyuvantes y como sistemas para la entrega de antígenos.…”
Section: Nanopartículas Poliméricasunclassified
“…The authors suggested that polymeric adjuvants may interact and activate various toll-like receptors and inframmasomes, thus involving several innate immature players in the ensuring immune responses [83] .…”
Section: Healing Of Pain and Nephrotoxicitymentioning
confidence: 99%